Against war: views from the underside of modernity - Maldonado Torres, Nelson (Latin America otherwise, 2008)
Introduction: Western modernity and the paradigm of war -- Searching for ethics in a violent world : a Jewish response to the paradigm of war -- From liberalism to Hitlerism : tracing the origins of violence and war -- From fraternity to altericity, or reason in the service of love -- Of masters and slaves, or Frantz Fanon and the ethico-political struggle for non-sexist human fraternity -- God and the other in the self-recognition of imperial man -- Recognition from below : the meaning of the cry and the gift of the self in the struggle for recognition -- From the ethical to the geopolitical : a Latin American response to coloniality, neoliberal globalization, and war -- Enrique Dussel's ethics and philosophy of liberation -- Enrique Dussel's contribution to the de-colonial turn : from the critique of modernity to transmodernity -- Conclusion: Beyond the paradigm of war. - Includes bibliographical references (p. [313]-333) and index. - Formerly CIP